Synergistic effects of combined motor and language interventions on stroke rehabilitation: a holistic approach - Saber-Moghadam, Reihaneh; Zeinalzadeh, Afsaneh; Jamali, Jamshid; Farzadfard, Mohammad Taghi; Sobhani-Rad, Davood (Frontiers in Human Neuroscience, 2024)
Background Stroke patients typically suffer from a range of symptoms, such as motor and language impairments, due to shared neural networks. The recovery process after stroke is intricate and requires a comprehensive approach. While previous studies have investigated the motor and language interventions independently, this study aimed to explore the relationship between these domains and compared the effectiveness of individual interventions versus their combined use. Methods We divided 45 stroke patients into three groups: Speech and Language Therapy (SLT) group; Arm Ability Training (AAT) group; and consecutive combination of SLT and AAT group. Participants attended 40-min sessions three days a week for three weeks. Standardized assessments, including picture naming test, syntactic comprehension test, and Test d’Evaluation des Membres Supérieurs de Personnes Âgées (TEMPA) test, were conducted pre-and post-treatment and during the first and second weeks of the intervention. Results Within-group comparisons demonstrated a significant enhancement in test scores for all groups post-intervention compared to pre-intervention (p < 0.05). Between-group comparisons revealed significant differences (p < 0.05) in performance on the picture naming test during the first week, the syntactic comprehension test in the second week, the functional rating subscale of Tempa test changes pre-and post-treatment and the first week, and the length of the time subscale of Tempa test improvements from pre-intervention to the first week. Conclusion Findings underscored the mutual and synergistic benefits of integrating motor and language in stroke rehabilitation. While SLT and AAT were effective when applied independently, their combined application yielded superior outcomes, emphasizing the holistic advantages of integrating these interventions, as supported by existing literature on dual-task rehabilitation strategies. Clinical trial registration https://irct.behdasht.gov.ir/search/result?query=IRCT20200114046134N1, IRCT20200114046134N1.